A multidisciplinary investigion of a sperm whale (physeter macrocephalus) mass stranding in italy - Mazzariol, Sandro; Petrella, Antonio; Troiano, Pasquale; Leonzio, Giuseppe; Giurisato, Maristella; Marcer, Federica; Vizzini, Salvatrice; Gaspari, Stefania; Pavan, Gianni; Podestà, Michela; Marsili, Letizia; Fossi, Maria Cristina; et al. (2011)
Mass strandings of sperm whales (Physeter macrocephalus) remain rather unexplained phenomena which rarely occur in the Mediterranean Sea. Many hypothesis have been advanced to explained them, both natural and induced by human activities. In December 2009, a group of seven young male sperm whales stranded on the Adriatic coast of Southern Italy. Complete necropsies or limited samplings were performed on the animals depending on the body condition. Natural causes and pathological changes associated with anthropogenic sonar activities were ruled out. Environmental pollutant s levels in sampled body tissues were relatively high, in particular organochlorinated substances (PCBs and DDT metabolites). Gastric content evaluation, coupled with morphologic tissue examination, showed a prolonged fasting which likely caused, at its turn, the mobilization of lipophylic contaminants from the adipose tissue. Chemical compounds subsequently entered the blood circulation impairing immune and nervous functions. Seismic surveys should be also regarded as potential co-factors, even if no evidence of direct impact has been assessed. Evaluation of meteorological and geographical data-set and historical records indicate that the group of young male sperm whales may have followed an erroneous path entering the Adriatic Sea. Guidelines useful to scientist for biologists and veterinarians facing similar circumstances raised from data obtained and the experience gained on the field.